Digital Readiness of Russian Regions - Naira P. BYCHKOVA; Zulay K. TAVBULATOVA; Natalya V. RUZHANSKAYA; Ruslan M. TAMOV; Evgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the study is to analyze the processes of digitalization at the regional level and determine the level of readiness of Russian regions for intensive digital development. The authors conducted a comparative analysis of Russian regions in terms of access of households and organizations to digital infrastructure, their use of digital technologies for personal and professional purposes, digital literacy, as well as investment in ICT development and R&D. The authors used the Portulance Institute methodology to determine the network readiness index of Russian regions. The available data from the Russian statistical database were grouped into subgroups - technology, people, governance, and impact. Calculations of the network readiness index for 80 regions of Russia were made by authors.  The results allowed to conclude that 32 regions of Russian Federation have high network readiness indicators. The proposed tools for assessing the network readiness of regions can be used as a criterion for differentiating digital development policies at both the state and regional levels.
Keywords: Digital Economy; Region; Russia; Digital Readiness; Network Readiness Index; Digital Infrastructure.